Avaliação da influência dos nanotubos de carbono nas propriedades da liga Al-2 % Si - SILVA, Hanathanya Rocha da (2022)
Due to the trend towards increased energy consumption, followed by frequent deterioration of cables and electrical transmission lines, research is being carried out on elements that increase resistance in electrically conductive alloys. The general objective of this work is to evaluate the influence of Carbon Nanotubes (CNT) on the Al-2% Si alloy. At first, Raman spectroscopy was performed on the functionalized NTC powder to start the alloy casting process in a cylindrical mold; After the solidification of the piece, it was cut and divided for lamination, which verified the macrostructure and microhardness tests, electrical conductivity, traction and SEM of the fracture were carried out; the unlaminated part was also checked for macrostructure and microhardness, and then the results were compared, in addition to observing the effect of heat treatment (TT). The Raman spectroscopy of the CNTs showed a proximity of the D and G bands, demonstrating the presence of amorphous carbons, in their ID/IG ratio an acceptable degree of disorder was revealed; in the macrostructures, a greater grain refinement was identified for the Al-2 % Si-NTC alloy; already in the microhardness, the Nanotubes present were responsible for the increase of this property; in terms of electrical conductivity, all alloys exceeded the 54.71% required by the IACS (International Annealed Copper Standard) for a final diameter of 3 mm to be considered electrically conductive alloys; in traction, alloys containing NTC also increased their values; in the SEM of the fractured region of the alloys with NTC, microcavities (dimples) of the shallower type and less ductility were found in relation to the untreated alloys; heat treatment was more evident in alloys without CNTs. All tests obtained gains in their properties in relation to alloys without heat treatments (STT) when subjected to the thermoresistivity test (230 °C and 280 °C), with the exception of the tensile strength limit (TRL), where only the alloy Al-2 % Si at 230 °C suitable according to the COPEL protocol. Finally, NTC gave the alloy greater mechanical strength and better electrical conductivity, but a decrease in ductility, allowing the alloy to be used within the electrical industry, since these were considered conductive.